THE VALIDITY OF CROSS-NATIONAL COMPARATIVE RATINGS AND GLOBAL BENCHMARKS FROM THE STANDPOINT OF COMPLEX INTERNATIONAL RELATIONS THEORY - V G Ivanov (RUDN Journal of Political Science, 2017)
The article discusses the validity of the leading cross-country comparative rankings and the global benchmarks from the standpoint of the theory of complex international relations theory. The pro-cesses of globalization provoke both universal schemes and projects, which are reflected in cross-country comparative indexes and benchmarks, and doubts about their validity due to the growing complexity and diversity of political institutions, values and systems in the contemporary world. The article analyses certain theoretical schools in political science, representing both of the aforementioned approaches.